Ruderal Plant Diversity as a Driver for Urban Green Space Sustainability - Daniela Mogîldea; Claudia Biță-Nicolae (Urban Science)
Urban development in south-eastern Europe has significant ecological consequences, such as a reduction in native plant diversity, the introduction of non-native species, and increased maintenance costs of urban green spaces. Achieving sustainable urban development requires a thorough understanding of the inventory of native plant species to better manage and conserve these areas. This study analyzed 806 vegetation surveys conducted in rural and urban areas over a 30-year period, identifying 450 plant species from 39 distinct plant communities. Our findings revealed generally low dominance index values in all communities, while Shannon diversity index values were particularly high, indicating rich species diversity despite urbanization pressures. Equality index values varied slightly, reflecting differences in species distributions. Principal component analysis (PCA) identified a substantial group of species with low abundance, which is essential for understanding and managing urban biodiversity. These findings have significant implications for urban planning and plant species conservation. Low dominance and high diversity suggest opportunities to improve urban green spaces by integrating diverse native species. In addition, the ecological and practical value of ruderal species, plants that thrive in disturbed environments, was emphasized, as well as their potential in medicine, phytoremediation, green roof design, and pollination services. Through directly correlating biodiversity indices with urban sustainability goals, our study provides useful insights for urban biodiversity management and the strategic integration of native plant species into urban landscapes.